2014
DOI: 10.1111/ajt.12918
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenic Expression of Human CD47 Markedly Increases Engraftment in a Murine Model of Pig-to-Human Hematopoietic Cell Transplantation

Abstract: Mixed chimerism approaches for induction of tolerance of solid organ transplants have been applied successfully in animal models and in the clinic. However, in xenogeneic models (pig-to-primate), host macrophages participate in the rapid clearance of porcine hematopoietic progenitor cells, hindering the ability to achieve mixed chimerism. CD47 is a cell-surface molecule that interacts in a species-specific manner with SIRPα receptors on macrophages to inhibit phagocytosis and expression of human CD47 on porcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 52 publications
1
56
0
Order By: Relevance
“…A likely reason for this clearance is that inhibition of phagocytosis through macrophage SIRPα receptor binding of CD47 on HC does not occur in the pig/primate combination 16;17 . Consistent with this hypothesis, we have previously demonstrated that transgenic expression of human CD47 (hCD47) substantially increases HC engraftment in a murine model of pig-to-human cell transplantation 18 .…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…A likely reason for this clearance is that inhibition of phagocytosis through macrophage SIRPα receptor binding of CD47 on HC does not occur in the pig/primate combination 16;17 . Consistent with this hypothesis, we have previously demonstrated that transgenic expression of human CD47 (hCD47) substantially increases HC engraftment in a murine model of pig-to-human cell transplantation 18 .…”
Section: Introductionmentioning
confidence: 60%
“…We previously reported the generation of a cloned transgenic miniature swine (18286) on an α-1,3-galactosyltransferase null (GalT-KO) background by recloning from a transgenic fetus (846-2) 18 . Both the fetus and 18286 demonstrated uniform expression of hCD47 on HC and fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD47 expression has prolonged the duration of porcine hematopoietic chimerism in baboons by inhibiting the phagocytosis of donor cells by primate macrophages. 80 Encouragingly, such prolongation has been associated with markedly prolonged donor swine skin xenografts. 81 …”
Section: The Future Of Transplantation Is Xenotransplantation and Itmentioning
confidence: 99%
“…In a fresh "live" pig aortic valve, macrophage infiltration could possibly be inhibited by transgenic expression of human CD47 [17,18], and pigs expressing human CD47 are now available in several centres. However, if the ultimate pig valve used for human heart valve surgery does need some glutaraldehyde fixation, then this may negate the biological activity of human CD47, and thus, alternative approaches may need to be investigated.…”
mentioning
confidence: 99%